EXCHANGE RATES AND THEIR IMPACT ON ECONOMIC GROWTH IN IRAQ FOR THE PERIOD 2004 – 2022 - Doctor. Abdullah Muhammad Rashid Al-Ramli; Assistant Lecturer: Marwa Abd Jawir Shamekh Al-Dulaimi; Prof. Dr. Nazhan Muhammad Sahu Hamdan (American Journals, 2024)
The research aims to clarify the effects that exchange rate fluctuations can have on economic growth in Iraq. One of the most prominent results that the research reached is that exchange rates explain 90% of the changes occurring in the gross domestic product, and the results of the Bound Test showed the co-integration between the variables of the study. If the calculated ( F ) is ( 6.79058 and is greater than the tabulated value, as it reached (4.6 6 ), at a significance level (5%), that is, the existence of a cointegration relationship between some variables , it showed results Impact in The term The short one that Fluctuations Prices Exchange ,as a variable independent may be I passed in Proof Its effect And the positive And Moral in Indicator Economic Growth (GDP) And at level Moral less From (0.05), i.e when the increase in Prices Exchange By 100% van Economic growth (GDP) rises By an amount 19 % , it showed results Impact in The term the long if that Fluctuations Prices Exchange ,as a variable independent did not succeed in Proof Its effect in Indicator Economic Growth (GDP) Because the probability exceeds the 5% barrier, the research is recommended to be important activation Role the bank Central In a way Larger from Okay monitoring the changes in Prices Exchange And strive the permanent to discount price Cashing Dinar Opposite Currencies The other and interest By factors Influential in price Exchange because Its effect Reflected In a way big on Prices Exchange.
Keywords: Exchange rate, gross domestic product.